Infant Weight Gain and School-age Blood Pressure and Cognition in Former Preterm Infants - Belfort, Mandy B. (2010)
OBJECTIVES: More rapid infant weight gain may be associated with better neurodevelopment but also with higher blood pressure (BP). The objective of this study was to determine the extent to which infant weight gain is associated with systolic BP (SBP) and IQ at school age in former preterm, low birth weight infants. METHODS: We studied 911 participants in the Infant Health and Development Program, an 8-center longitudinal study of children born at ≤37 weeks' gestation and ≤2500 g. Study staff weighed participants at term and at 4 and 12 months' corrected ages; measured BP 3 times at 6.5 years; and administered the Wechsler Intelligence Scale for Children, Third Edition (WISC-III), an IQ test, at 8 years. In linear regression, we modeled our exposure “infant weight gain” as the 12-month weight z score adjusted for the term weight z score. RESULTS: Median (interquartile range) weight z score was −0.7 (−1.5 to −0.0) at 12 months. Mean ± SD SBP at 6.5 years was 104.2 ± 8.4 mm Hg, and mean ± SD WISC-III total score at 8 years was 91 ± 18. Adjusting for child gender, age, and race and maternal education, income, age, IQ, and smoking, for each z score additional weight gain from term to 12 months, SBP was 0.7 mm Hg higher and WISC-III total score was 1.9 points higher. CONCLUSIONS: In preterm infants, there seem to be modest neurodevelopmental advantages of more rapid weight gain in the first year of life and only small BP-related effects.